Specific Physical Exercise Improves Energetic Metabolism in the Skeletal Muscle of Amyotrophic-Lateral- Sclerosis Mice - Desseille, Céline; Deforges, Séverine; Biondi, Olivier; Houdebine, Léo; D’amico, Domenico; Lamazière, Antonin; Caradeuc, Cédric; Bertho, Gildas; Bruneteau, Gaëlle; Weill, Laure; Bastin, Jean; Djouadi, Fatima; et al. (Frontiers in Molecular Neuroscience, 2017)
Amyotrophic Lateral Sclerosis is an adult-onset neurodegenerative disease characterized by the specific loss of motor neurons, leading to muscle paralysis and death. Although the cellular mechanisms underlying ALS-induced toxicity for motor neurons remain poorly understood, growing evidence suggest a defective energetic metabolism in skeletal muscles participating in ALS-induced motor neuron death ultimately destabilizing neuromuscular junctions. In the present study, we report that a specific exercise paradigm, based on a high intensity and amplitude swimming exercise, significantly improves glucose metabolism in ALS mice. Using physiological tests and a biophysics approach based on Nuclear Magnetic Resonance (NMR), we unexpectedly found that SOD1(G93A) ALS mice suffered from severe glucose intolerance, which was counteracted by the high intensity swimming protocol but not by the moderate intensity running protocol. Furthermore, the swimming-based training restored the highly ALS-sensitive tibialis muscle through an autophagy-linked mechanism involving the expression of key glucose transporter and metabolic enzymes, including GLUT4 and glyceraldehyde-3-phosphate dehydrogenase (GAPDH). Importantly, these molecular defects were also found in muscles from ALS patients. Moreover, we report that the swimming program induced a triglyceride accumulation in ALS tibialis, likely resulting from an increase in the expression levels of lipid transporters and biosynthesis enzymes, notably DGAT1 and related proteins. All these data provide the first molecular basis for the differential effects of specific exercise type and intensity in ALS, calling for the use of physical exercise as an appropriate intervention to alleviate symptoms in this debilitating disease.